The Influence of Academic Supervision and Teacher Professionalism on the Quality of Learning - Anggraeni, Lisa; Kusumaningsih, Widya; Soedjono, Soedjono (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study examines the influence of academic supervision and teacher professionalism on the quality of learning at public elementary schools in Warungpring District, Pemalang Regency. A quantitative correlational approach was used involving 117 teachers selected proportionally. Data were collected through Likert-scale questionnaires measuring teachers’ perceptions of academic supervision, teacher professionalism, and learning quality. Data analysis employed simple and multiple linear regression to test the partial and simultaneous effects of the independent variables on the dependent variable. The results showed that academic supervision had a regression coefficient of 0.602, indicating that every one-unit increase in structured supervision would improve learning quality by 0.602 units. Teacher professionalism also had a regression coefficient of 0.650, meaning that a one-unit increase in ongoing professional development would raise learning quality by 0.650 units. Simultaneously, these two variables contributed 72.6% to the variation in learning quality at the elementary schools. These findings emphasize the importance of structured supervision and ongoing professional development as key strategies for improving learning quality. The study recommends that school principals and education policymakers focus on enhancing these two aspects through continuous training, mentoring, and evaluation programs to support effective learning processes. Further research is also suggested to include other potential variables influencing learning quality to obtain more comprehensive results.